Self-reported work-related accumulative fatigue of nurses: A cross-sectional study in public hospitals in China - Tang, Changmin; Chen, Xin; Gong, Guangwen; Guan, Cuiling; Liu, Chaojie (Frontiers in Public Health, 2022)
Objectives: Work-related fatigue is a serious safety risk to nurses and their patients. This study aimed to assess self-reported work-related accumulative fatigue of nurses and its associated factors. Methods: A questionnaire survey of 2918 clinical nurses conveniently sampled from 48 public hospitals across six provinces in China was conducted. The “Self-diagnosis Checklist for Assessment of Workers’ Accumulated Fatigue” was adopted to assess the level of work-related accumulative fatigue of the study participants. Chi-square tests and ordinal regression analyses were performed to determine the sociodemographic characteristics associated with work-related accumulative fatigue. Results: About one third of respondents reported low work-related accumulative fatigue, compared with 23.1% reporting high and 24.6% reporting very high levels of work-related accumulative fatigue. Higher levels of work-related accumulative fatigue were associated with female gender (AOR=0.614 for male relative to female, p=0.005), age between 30 and 40 years (AOR=1.346 relative to >40 years, p=0.034), 5-10 years of work experience (AOR=1.277 relative to >10 years, p=0.034), and bachelor or above degree qualifications (AOR=0.806 for associate degree relative to bachelor or above degree, p=0.007). Those who worked in rural county hospitals (AOR=0.816 for metropolitan relative to rural county hospitals, p=0.006) and resided in central China (AOR=1.276 relative to western China, p=0.004) had higher odds of reporting higher levels of work-related accumulative fatigue. Conclusion: High levels of work-related accumulative fatigue are evident in nurses of public hospitals in China. The problem is more serious in the female nurses in their mid-career and those who worked in the central region and rural setting.